Antidepressant effects of valproic acid in an animal model of depression - Buzgoova K.; Balagova L.; Hlavacova N.; Jezova D. (European Pharmaceutical Journal, 2019)
Valproic acid, beside its anticonvulsant action, is widely used as a mood stabilizer in the therapy of bipolar disorder. The potential antidepressant action of valproic acid has not been sufficiently characterized so far. The aim of the present study was to evaluate the antidepressant effect of valproic acid in an aldosterone model of depression. Subchronic treatment with valproic acid resulted in a reduction of the time spent in immobility in the forced swim test. In conclusion, the present study provides evidence on antidepressant effects of valproic acid using a classical behavioral approach for testing the efficacy of antidepressant drug in animal models.